Combined Ischemic and Hemorrhagic Stroke Care in Stroke Unit: Development and Effectiveness, Buriram Hospital - มัดจุปะ, วุฒิชัย; กองเงิน, ลิสา; นพตลุง, สายหยุด (Thai Journal of Neurological Surgery, 2025)
Background: The Service Plan of the Ministry of Public Health policy assigns every tertiary hospital establishes stroke unit with aims to reduce the mortality rate. However, there are a few hospitals developed combined ischemic and hemorrhagic stroke unit. Objective: To study the development process and the effectiveness of the stroke unit where both ischemic and hemorrhagic stroke were admitted. Method: A research and development study was conducted in all stroke patients who were admitted from December 2014 to June 2018. The development included 5 phases; analyzing the situation prior to setting up the stroke ward, developing the model of patient care, implementing the developed model, revising and utilizing the new one, and evaluating the development of stroke ward. Descriptive statistics, frequency, percentage, mean values and content analysis were used to analyze data. Result: There are 28 beds in the ward, 8 for critical care and 20 for acute phase patients. There are 20 nurses 16 of which passed basic stroke care course. The primary medical team is comprised of 2 neurologists and 5 neurological surgeons providing patient care according to Buriram stroke guidelines. Approximately 87.4% of stroke patients (5,618 of 6,429) were admitted to stroke ward, 91.9% (4,154 of 4,520) was ischemic stroke and 76.7% (1,464 of 1,909) was hemorrhagic stroke. Overall stroke mortality rate was reduced from 8.4% to 5.5% (p < 0.001). For the ischemic stroke and the hemorrhagic stroke subgroup, the mortality rate was reduced from 3.9% to 2.0% (p = 0.001) and from 18.2% to 14.2% (p = 0.045), respectively. Conclusion: Combining ischemic and hemorrhagic stroke care in the stroke ward improves patient care and significantly reduced stroke mortality rate. The key factor for success is the effective collaboration between neurologists, neurosurgeons and multidisciplinary teams.